MANAGEMENT OF INTANGIBLE ASSETSS OF THE ENTERPRISE INNOVATIVE PERFORMANCE WITH REFERENCE TO RISKS - Irina Vladimirovna Elokhova (Science and Innovation Center Publishing House, 2019)
The article is devoted to the analysis of existing assessment tools of intangible results of innovative performance that are used to manage the innovative development of the enterprise. The authors consider the most common methods for determining the risk premium when calculating the discount rate. The study shows that existing methods take into account intangible results to a different extent. At the same time, not all intangible results of innovative performance and not in all methods are taken into account properly, this proves that accounting of intangible results can change the discount rate and affect the future cash flows of the enterprise and, as a consequence, the value of the enterprise.